1994
DOI: 10.1159/000109544
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein in Developing Human Brain

Abstract: Localization of metallothionein (MT) in the developing human brain was investigated by immunohistochemical techniques. Fetal brain at 21 weeks showed no MT expression. In 35-week-old fetuses, glial cells in the gray matter showed MT expression in the nucleus and perinuclear cytoplasm, but glial cells in the white matter showed MT not only in the nucleus and perinuclear cytoplasm but also in glial processes. At 40 weeks, glial cells in gray and white matter expressed immuno-reactive MT in the nucleus, cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
1
17
0
4
Order By: Relevance
“…This is in agreement with previous observations reporting that MT is expressed only in minute amounts in the embryonic and neonatal rodent brain and that its expression progressively increases during the first weeks w x of the postnatal development 43,59 . In addition to age-related differences, MT is not uniformly distributed through the normal CNS and regional differences in the MT prow x tein and MT mRNA content 14,20,21,25,28 , as well as in w x the distribution of MT-positive cells 8,28 , have been described.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 93%
“…This is in agreement with previous observations reporting that MT is expressed only in minute amounts in the embryonic and neonatal rodent brain and that its expression progressively increases during the first weeks w x of the postnatal development 43,59 . In addition to age-related differences, MT is not uniformly distributed through the normal CNS and regional differences in the MT prow x tein and MT mRNA content 14,20,21,25,28 , as well as in w x the distribution of MT-positive cells 8,28 , have been described.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 93%
“…In mice, MT-IV is not detected prior to day 7 postpartum (17). Furthermore, MT is not detected in human fetal brain in less than the 35-week-old fetus (89). The mechanisms responsible for developmental regulation of MT transcription have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of in situ hybridization (21, 24-28) and immunohistochemistry (19,21,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), have demonstrated that MT-1&2 expression occurs throughout the brain and spinal cord, and that the principal cellular source is the astrocyte, particularly following injury. Significant MT-1&2 expression is also found in ependymal cells, epithelial cells of the choroid plexus, meningeal cells of the pia mater and endothelial cells of blood vessels, while neurons appear to express very low levels.…”
Section: Metallothionein-1and2 Are Preferentially Expressed In Reactivementioning
confidence: 99%